Exercise training-induced modification of the gut microbiota persists after microbiota colonization and attenuates the response to chemically-induced colitis in gnotobiotic mice. (4th March 2018) - Allen, J. M.; Mailing, L. J.; Cohrs, J.; Salmonson, C.; Fryer, J. D.; Nehra, V.; Hale, V. L.; Kashyap, P.; White, B. A.; Woods, J. A.
ABSTRACT: Exercise reduces the risk of inflammatory disease by modulating a variety of tissue and cell types, including those within the gastrointestinal tract. Recent data indicates that exercise can also alter the gut microbiota, but little is known as to whether these changes affect host function. Here, we use a germ-free (GF) animal model to test whether exercise-induced modifications in the gut microbiota can directly affect host responses to microbiota colonization and chemically-induced colitis. Donor mice (n = 19) received access to a running wheel (n = 10) or remained without access (n = 9) for a period of six weeks. After euthanasia, cecal contents were pooled by activity treatment and transplanted into two separate cohorts of GF mice. Two experiments were then conducted. First, mice were euthanized five weeks after the microbiota transplant and tissues were collected for analysis. A second cohort of GF mice were colonized by donor microbiotas for four weeks before dextran-sodium-sulfate was administered to induce acute colitis, after which mice were euthanized for tissue analysis. We observed that microbial transplants from donor (exercised or control) mice led to differences in microbiota β-diversity, metabolite profiles, colon inflammation, and body mass in recipient mice five weeks after colonization. We also demonstrate that colonization of mice with a gut microbiota from exercise-trained mice led to an attenuated response to chemical colitis, evidenced by reduced colon shortening, attenuated mucus depletion and augmented expression of cytokines involved in tissue regeneration. Exercise-induced modifications in the gut microbiota can mediate host-microbial interactions with potentially beneficial outcomes for the host.